2016
DOI: 10.18632/oncotarget.9848
|View full text |Cite
|
Sign up to set email alerts
|

Improved therapeutic outcomes of thermal ablation on rat orthotopic liver allograft sarcoma models by radioiodinated hypericin induced necrosis targeted radiotherapy

Abstract: Residual tumor resulting in tumor recurrence after various anticancer therapies is an unmet challenge in current clinical oncology. This study aimed to investigate the hypothesis that radioiodinated hypericin (131I-Hyp) may inhibit residual tumor recurrence after microwave ablation (MWA) on rat orthotopic liver allograft sarcoma models.Thirty Sprague-Dawley (SD) rats with hepatic tumors were divided into three groups: Group A received laparotomy MWA and sequential intravenous injection (i.v.) of 131I labelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…10 In order to improve hypericin biodistribution for use in necrosis affinity, a variety of delivery methods have been used in previous studies, including solubilizing in organic solvents such as DMSO, or admixture with PEG 400, propylene glycol, and sodium cholate. 26,27 We incorporated a biodegradable PEG-PCL polymer shell to produce a highly biocompatible and soluble nanoplatform encapsulating gold nanoparticles and hypericin. PEG-PCL involves di-block copolymers with both hydrophilic and hydrophobic components capable of generating watersoluble nanoparticles with a hydrophobic core and hydrophilic shell in aqueous solutions.…”
Section: Synthesis Of Au-hyp-npmentioning
confidence: 99%
“…10 In order to improve hypericin biodistribution for use in necrosis affinity, a variety of delivery methods have been used in previous studies, including solubilizing in organic solvents such as DMSO, or admixture with PEG 400, propylene glycol, and sodium cholate. 26,27 We incorporated a biodegradable PEG-PCL polymer shell to produce a highly biocompatible and soluble nanoplatform encapsulating gold nanoparticles and hypericin. PEG-PCL involves di-block copolymers with both hydrophilic and hydrophobic components capable of generating watersoluble nanoparticles with a hydrophobic core and hydrophilic shell in aqueous solutions.…”
Section: Synthesis Of Au-hyp-npmentioning
confidence: 99%
“…Hypericin was originally thought to be a tumor-seeking agent, but afterward it turned out to be a necrosis-avid agent. Although radionuclide-labeled hypericin was extensively studied for visualization of myocardial necrosis and targeted therapy of tumors, there was only one report that radionuclide-labeled hypericin was used for noninvasive evaluation of tumor response to therapy, in which 64 Cu-labeled bis-DOTA-hypericin ( 64 Cu-bis-DOTA-hypericin) was shown to be capable of monitoring tumor damage caused by photothermal ablation therapy . Notwithstanding that the authors thought the avidity of 64 Cu-bis-DOTA-hypericin for damaged tissues might be due to its selective binding to exposed PS or PE, our recent research demonstrated that the necrosis avidity of hypericin-based molecular probes was more likely to result from their interaction with exposed DNA …”
Section: Necrosis Imagingmentioning
confidence: 99%
“…Apart from its potential for imaging necrotic myocardium after labeled with iodine-12354., 55., 56., Hyp had also been extensively explored for the treatment of diverse solid tumors or evaluation of therapeutic efficacy after labeled with iodine-131 or copper-64 (Fig. 1)57., 58., 59., 60., 61., 62., 63., 64., 65.. Despite the substantial translational potential related to certain oncological and non-oncological applications 66 , some inherent defects such as extremely poor water solubility, easy to form aggregates and deep colors may haunt its further clinical transformation.…”
Section: Molecular Imaging and Therapeutic Strategies Targeting Necromentioning
confidence: 99%